Perubahan Strategi Rumah Sakit di Era Pandemi Covid 19 : Literature Review - Andara Dwike (Jurnal Medika Hutama, 2023)
Abstract The COVID-19 pandemic has turned the health of the industry upside down and accelerated many ideas that will be realized for the future and some that took decades to realize. Hospitals that previously had plans for their business strategy had to work hard to adapt and even change their strategy on a large scale and dramatically. The expected short and fast adaptation to hospital management must be supported by all elements of the hospital down to individual health workers to support changes in hospital strategy in order to maintain the hospital's strength to survive in an uncertain era such as the dynamics of the COVID-19 pandemic